(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In interconnected power system stability is influenced by oscillations. The safe functioning of these systems depends on the damping of these oscillations. The development of the damping controllers is a constraint-based on a multimodal optimization problem. The use of conventional optimization methods is relatively difficult. In this paper, a power system stabilizer that generates an additional control signal for the excitation system provides the improvement of the stability of the Single Machine Infinite Bus System (SMIB). To overcome the disadvantages of conventional power system stabilizers (CPSS), a PSS controller is designed. The structure of a conventional controller PID is used, where the gains are adapted online based on parameter estimation using fuzzy gain scheduling. A genetic algorithm (GA) is used to determine the range of the controller parameters. The simulation results show the high performance of the proposed controller, to improve the stability of the power system compared to conventional PSS.